PERANCANGAN SISTEM INFORMASI PEMESANAN KAMAR KOST PADA RUKOST AYAH BUNDA MENGGUNAKAN METODE DESIGN THINKING - Nurul Fitrah Hayati; Arie Rafika Dewi; Fachrul Rozi Lubis (Universitas Methodist Indonesia, 2022)
With respect to the development of information technology, and would force the people in those who use the technology maximally life of all terms. Certainly various information, one is for the students who will undergo tour study or undergo college them in the far from their homes. It made students were to will find temporary shelter as a domicile for the study done. It is therefore needed a system by which can help students to rented room without coming directly to tenants. Building these systems in a design thinking from empathizing, defining, ideating, and testing prototype. Of writing code PHP, using the program and also use database MySQL framework Codeigniter 3. With the rental system, the rooming house is to simplify prospective tenants to do the booking the rooming house without having to come to the rooming house providers.